Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Contrasting Population Trajectories of Temperate Reef Fishes and Invertebrates Following Seasonal and Multi‐Decadal Temperature Change - Yann Herrera Fuchs; Graham J. Edgar; Neville S. Barrett; Lara Denis‐Roy; Shenae Y. Willis; Hunter Forbes; Rick D. Stuart‐Smith (Global Change Biology, 2025)
Temperature perturbations from climate change affect ecosystems through short‐term pulse events, such as heatwaves, and chronic long‐term shifts. Temperate rocky reef ecosystems have been observed to show substantial ecological change as a result of short‐term temperature fluctuations, but the longer‐term impacts of temperature change remain poorly understood. Here, we investigate temperate reef fishes and mobile invertebrates along Tasmania's east coast, contrasting trends in species richness, abundance, and community structure across seasons within a year to those observed over three decades of warming. Fishes exhibited dynamic seasonal shifts, but interannual changes in richness and abundance balanced out over decades with limited overall net change. In contrast, invertebrate communities changed little seasonally but suffered significant long‐term losses. Our study revealed short‐term ecological changes driven by temperature to be incongruent with long‐term shifts. Species responded in varying ways, depending on life history and ecology. Fishes apparently tracked short temperature pulses, while less mobile invertebrates, such as echinoderms and molluscs, tolerated short‐term fluctuations but exhibited long‐term decline. Multi‐scale studies across a broad range of taxa are needed to clarify thermal responses. The most vulnerable taxa—those facing long‐term thermal stress—may be overlooked through decisions based on short‐term studies, risking major biodiversity loss.

The Associations Between Neuropsychiatric Symptoms and Cognition in People with Dementia: A Systematic Review and Meta-Analysis - Julieta Sabates; Wei-Hsuan Chiu; Samantha Loi; Amit Lampit; Hanna M. Gavelin; Terence Chong; Nathalie Launder; Anita M. Y. Goh; Amy Brodtmann; Nicola Lautenschlager; Alex Bahar-Fuchs (Neuropsychology Review, 2024)
Most people with dementia experience neuropsychiatric symptoms (NPS), including anxiety, depression or disinhibition. There is growing interest in the relationship between NPS and cognitive impairment, but data is still limited. This study aimed to investigate the specific associations between NPS and cognition in people with dementia. MEDLINE, EMBASE and PsycINFO were searched for published, peer-reviewed studies of associations between at least one NPS and one cognitive ability in people with dementia. The quality of the studies was assessed with the NIH National Heart, Lung and Blood Institute’s quality assessment tools. A meta-analysis was conducted using Robumeta package for R. Ninety studies were included. We found significant associations between NPS, global cognition and cognitive domains, e.g. apathy was associated with global cognitive and memory impairment; dysphoria was associated with worse attention; delusions with executive dysfunction. Increased NPS in people with dementia are associated with worse cognitive performance. There were few studies looking at associations between some neuropsychiatric clusters and cognitive abilities, and there was little research on causal relationships. Our review was limited by the inclusion of studies that reported associations in specific formats, and most included people with a diagnosis of Alzheimer’s disease (AD). However, given the large number of studies, this is unlikely to have biased results. More research is needed that includes diverse people with different dementia syndromes. Registration: PROSPERO 2020 CRD42020165565.

Genome‐wide SNPs confirm plumage polymorphism and hybridisation within a Cyornis flycatcher species complex - Elize Y. X. Ng; Siqi Li; Dezhi Zhang; Kritika M. Garg; Gang Song; Jonathan Martinez; Le Manh Hung; Vuong Tan Tu; Jérôme Fuchs; Lu Dong; Urban Olsson; Yuan Huang; et al. (Zoologica Scripta, 2023)
Morphology has been a leading taxonomic guiding light to systematists for the last couple of hundred years. However, the genetic and – more recently – genomic revolution have produced numerous demonstrations of erroneous classifications that were based on labile morphological traits. We used thousands of genome‐wide markers to shed light on evolutionary dynamics in a confusing and taxonomically obscure group of Asian Cyornis flycatchers. Using genomic data, we corroborated recent findings based on three mitochrondrial and five nuclear genes that the two taxa hainanus and klossi which were previously treated as separate species ( Cyornis hainanus and Cyornis rubeculoides klossi , respectively) are genomically homogeneous and form a single species, C. hainanus . We also uncovered a novel case of interbreeding between C. hainanus and a non‐sister species, C. glaucicomans , illustrating these flycatchers' ability to hybridise in marginal situations even after substantial times of divergence. Our study illustrates how genome‐wide loci can shed light on complicated taxonomic problems, resulting in a better integration of phenotypic and genotypic data.

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

Chemical composition of tourmaline from the Asarcık Pb–Zn–Cu ± U deposit, Şebinkarahisar, Turkey - F. Yavuz; Y. Fuchs; N. Karakaya; M. Ç. Karakaya (Mineralogy and Petrology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

De-regulation of ubiquitin-dependent proteolysis and the pathogenesis of malignant melanoma - Serge Y. Fuchs (Cancer and Metastasis Reviews, 2005)

Neuromodulation for behavior in the locust frontal ganglion - Y. Zilberstein; E. Fuchs; L. Hershtik; A. Ayali (Journal of Comparative Physiology A, 2004)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Mössbauer and infrared spectrometry of lizardite- 1T from Monte Fico, Elba - Y. Fuchs; J. Linares; M. Mellini (Physics and Chemistry of Minerals, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)